CHARACTER EDUCATION ASSISTANCE FOR AUTISM AT THE NON-PROFIT FOUNDATION - Risma Fahrul Amin; Syaiful Ma'ruf (Jurnal Pendidikan (Teori dan Praktik), 2024)
The aim of this research is Character Education Assistance for Autism at the Non-Profit Foundation Cinta Harapan Indonesia (YCHI) Madiun. This type of research method is qualitative. Data collection using interviews, observation and documentation. Data analysis using triangulation. Character education assistance for autistic children at the Non-Profit Cinta Harapan Indonesia Foundation (YCHI) Madiun has had a significant impact in forming their positive character. The program includes a structured and caring approach, with a focus on developing social, emotional and moral skills through a variety of activities tailored to each individual's needs. Accompaniment that is carried out consistently and with a participation-based approach allows autistic children to increase their self-understanding, socialize better, and develop positive values that can support them in interacting in social environments. In this way, this program not only benefits children's personal development, but also creates an inclusive environment and supports them to reach their best potential.